Dropout in High Schools students–Modeling a Case Study in the Vhembe District, Limpopo Province, South Africa - Kyei, Kwabena A. (Journal of Education and Vocational Research, 2014)
South Africa experiences a significant amount of dropouts of high school learners every year. Only about 45% of learners who start primary school in a given year write matriculation examinations after 10 years of schooling. A high dropout rate deprives the country of well-informed and competent future leaders. This study looks at the factors that underlie dropout in high schools in the Vhembe district. A random sample of 5 villages was selected from 25 villages which have high schools. A census of high school dropouts in these 5 villages was conducted. About 660 dropouts were obtained and interviewed. Applying regression modeling, this study shows that poor performance, attitude, punishment and pregnancy are the factors affecting dropout in Vhembe, and recommends that educators encourage learners to develop positive attitude to school work and also give extra assistance to under-performing learners, and sex education be given with seriousness to reduce unwanted pregnancies.